Using virtual reality for teacher education: a systematic review and meta-analysis of literature from 2014 to 2024 - Han, Xue; Luo, Heng; Wang, Zi; Zhang, Dongyu (Frontiers in Virtual Reality, 2025)
The global demand for qualified teachers continues to rise, yet conventional training models often fall short in offering scalable, inclusive, and practically rich learning experiences that prepare educators for real-world classroom challenges. Virtual reality (VR) is increasingly recognized as a transformative tool in teacher education, offering immersive, interactive, and repeatable environments that support procedural rehearsal, affective engagement, and reflective practice. However, existing research remains fragmented, with few studies providing a comprehensive review of VR’s application in teacher education, its overall effectiveness, and the factors that influence learning objectives. This study systematically reviewed 52 empirical studies published between 2014 and 2024, including 22 experimental and quasi-experimental designs, which were further synthesized through meta-analysis to evaluate the overall effectiveness of VR-supported instruction. The results indicate a positive moderate overall effect of VR in teacher education (Hedges’ g = 0.524), with significant variations based on immersion level, equipment type, and learning objectives. These findings offer strong evidence for integrating VR into both pre-service and in-service teacher training and highlight its potential to support accessible, adaptive, and scalable professional development. The study provides practical implications for practitioners, teacher educators, and VR developers seeking to align VR tools with diverse learning needs in teacher preparation.